Somatosensory evoked magnetic fields induced by electrical palate stimulation in patients with unilateral cleft lip and palate after palatoplasty. (November 2022) - Shimada, Eriya; Hihara, Hiroki; Kitayama, Chihiro; Kanno, Akitake; Kawashima, Ryuta; Sato, Akimitsu; Imai, Yoshimichi; Nakasato, Nobukazu; Igarashi, Kaoru; Kanetaka, Hiroyasu
Abstract: Palatal sensation is important for articulation, feeding, and swallowing. However, palatal sensation in patients with cleft palate (CP) after palatoplasty has been investigated only inadequately because of the complexity and high costs of objective evaluation. This study compared the somatosensory evoked magnetic fields (SEFs) induced by electrical stimulation of the palates of patients with CP after palatoplasty and the palatal sensory thresholds (PSTs) of the stimulation with those of healthy (control) subjects. The CP group comprised 12 patients with unilateral cleft lip and palate (UCLP). The control group comprised 31 control subjects. No significant difference in intensity was found between them. Nevertheless, the PSTs in the UCLP group were significantly higher than those in the control group at all sites ( p  < 0.05). We infer that the electrical signals transmitted from palatal sensory receptors of patients with CP might be amplified by a compensation mechanism in the central nervous system. SEFs provide an effective method for objective evaluation of palatal sensation in patients with CP after palatoplasty. Evaluation of SEFs during palatal sensory stimulation in patients with CP after palatoplasty might lead to better corrective surgical methods that also preserve palatal sensation. Highlights: SEF latency in the palate is longer in UCLP patients than in healthy subjects. SEF intensity shows no difference between UCLP patients and healthy subjects. PSTs are higher in UCLP patients than in healthy subjects at all palate sites. SEF measurement is an effective objective method for evaluating palatal sensation.